Effects of space allocations and energy levels on growth performance and nutrient digestibility in growing and finishing pigs. Issue 1 (15th May 2017) - Lei, X. J.; Yan, L.; Kim, Y. M.; Kim, I. H.
Summary: Two experiments were conducted to investigate effects of different space allocations and different dietary metabolizable energy (ME) levels on growth performance and nutrient digestibility in growing and finishing pigs. In experiment 1, a total of 84 growing pigs [(Yorkshire × Landrace) × Duroc] with an initial body weight (BW) of 27.10 ± 1.60 kg were used in a 5‐week trial. Pigs were blocked based on initial BW into a 2 × 2 factorial design with the following factors: (i) 0.60 or 0.80 m 2 /pig space allocations; and (ii) 3, 400 or 3, 550 kcal/kg ME of diets. In experiment 2, a total of 84 finishing pigs with an initial BW of 67.43 ± 1.97 kg were used in a 10‐week trial. Pigs were allotted based on initial BW into a 2 × 2 factorial design with the following factors: (i) 0.81 or 1.08 m 2 /pig space allocations; and (ii) 3, 300 or 3, 450 kcal/kg ME of diet. In experiment 1, high ME diet improved gain‐to‐feed ratio (G:F) in pigs with low space allocation but not in pigs in high space allocation ( p < .05). Additionally, high ME diet increased apparent total tract digestibility (ATTD) of nitrogen in low space allocation but decreased ATTD of nitrogen in high space allocation ( p < .05). In experiment 2, high ME diet improved average daily gain (ADG) and G:F in early‐finishing pigs with low space allocation but not in pigs with high space allocation ( p < .05). In conclusion, the provision of high ME diets was not enough to overcome the reduction in growth performance due to low space allocation but can improve feed efficiency in growing pigs and daily gain and feed efficiency early‐finishing pigs.